2021
DOI: 10.7759/cureus.14134
|View full text |Cite
|
Sign up to set email alerts
|

Examining Healthcare Workers’ Perspectives Concerning Medical Equipment Availability in Three Ethiopian Hospitals: A Qualitative Pilot Study

Abstract: BackgroundHospitals in the United States often have an abundance of unused medical supplies and equipment while many developing countries are in considerable need of these resources. Many nongovernmental organizations (NGOs) have donated medical equipment to health centers in low-resource settings to rectify this issue; however, studies show many of these donations are not usable by the facilities that receive them. To better serve the partner hospitals of our NGO, Oasis Medical Relief, we investigated the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Here in Ethiopia, medical supplies, including lifesaving medications, were scarce. 25,34 Conversely, a study conducted in Pakistan reported a higher ICU mortality rate (77%). 19 The possible justification could be that the Pakistan study was conducted in the earliest waves of the pandemic, where countries lack readiness and inconsistent management protocols that might significantly influence patient outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Here in Ethiopia, medical supplies, including lifesaving medications, were scarce. 25,34 Conversely, a study conducted in Pakistan reported a higher ICU mortality rate (77%). 19 The possible justification could be that the Pakistan study was conducted in the earliest waves of the pandemic, where countries lack readiness and inconsistent management protocols that might significantly influence patient outcomes.…”
Section: Discussionmentioning
confidence: 97%